Dermoscopy of eruptive vellus hair cyst - Ferreira, Cesar Augusto Zago [UNESP]; Alvares, Bruno Augusto [UNESP]; Lacerda, Priscila Neri [UNESP]; Miot, Helio Amante [UNESP] (GN1 Sistemas e Publicacoes, 2022)
Eruptive vellus hair cyst is a rare and benign dermatological condition in the development of vellus-type hair follicles. It affects mainly children and young adults, and is characterized by multiple asymptomatic papules, especially on the trunk. We report the case of a 33-year-old white man who presented multiple erythematous papules and pustules located on the trunk for about five years, refractory to topical treatments for acne. Dermoscopy revealed oval lesions with eccentric exulceration and rare protruding filiform structures. We established the diagnosis of eruptive vellus hair cyst based on the findings of dermoscopy and histopathological examination
Dermatoscopia do cisto veloso eruptivo
Keywords: Acneiform eruptions; Cysts; Hiv